USE OF ISOTOPE DILUTION METHOD FOR DETERMINATION OF Ce, Sm, AND Yb ABUNDANCES IN GEOLOGICAL SAMPLES BY ICP-MS - Cao Đông Vũ; Trương Đức Toàn; Nguyễn Đăng Khánh; Đỗ Tâm Nhân; Võ Trần Quang Thái; Nguyễn Lê Anh; Nguyễn Việt Đức; Nguyễn Giằng; Nguyễn Trọng Ngọ (Tạp chí Khoa học Đại học Đà Lạt)
In this study, we used the ID-ICP-MS technique to determine the concentration of Ce (LREE), Sm (MREE), and Yb (HREE) in three geological, certified reference materials: BHVO-2, BCR-2, and NIST 2711a. Calibration experiments using the ID technique, such as concentration calibration and relative isotopic abundance calibration for spike solutions, were conducted experimentally. In addition, mass spectral interferences and mass fractionation in ICP-MS were also investigated, corrected and discussed. For the first time in Vietnam, ID-ICP-MS has been successfully applied to determine three rare earth elements Ce, Sm, and Yb in basaltic geological samples (BHVO-2 and BCR-2) with high accuracy and reproducibility (<5%). For NIST SRM 2711a with soil matrix, the results of the accuracy and reproducibility were approximately 10%, except for the result obtained for Ce, with a dilution factor of 3000, which was 15.4% lower than the published value.